Penguatan Profil Pelajar Pancasila Melalui Model VCT Tipe Daftar Baik Buruk Pada Pendidikan Pancasila Sekolah Dasar - Dinda Sarono Putri; Maha Latasa Buju Basafpipana Habaridota; Syarifah Asmiati (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2025)
The aim of this research is to describe the strengthening of the Pancasila learner profile using the Value Clarification Technique (VCT) model with the good and bad list type in Pancasila education, specifically in the topic of obeying school rules for grade II learners at State Elementary School 03 East Pontianak in the 2024/2025 academic year. The method used is descriptive with a qualitative approach. The data source for this research is the grade II B teacher at State Elementary School 03 East Pontianak. Based on the analysis conducted, the researcher concludes that: The planning carried out by the grade II B teacher aligns with the Value Clarification Technique (VCT) model of the good and bad list type, which includes a teaching module, reinforcement of the Pancasila learner profile, and planning within the learner worksheet (LKPD); The implementation of the Value Clarification Technique (VCT) model of the good and bad list type has enabled the teacher to successfully deliver lessons that not only teach the material on obeying rules but also shape learners’ character in accordance with Pancasila values; The evaluation process is in accordance with the Value Clarification Technique (VCT) model of the good and bad list type and includes aspects of affective assessment. The positive impact of this research is that the use of the Value Clarification Technique (VCT) model with the good and bad list type has led to better reinforcement of the Pancasila learner profile, particularly in the aspect of mutual cooperation